Neonatal morbidity and mortality in a Rural Tertiary Hospital in Nigeria - Umma Idris Abdullahi (Wolters Kluwer Medknow Publications, 2018)
Background: Nigeria is one of the greatest contributors to the neonatal morbidity and maternity worldwide. Objective: This study was undertaken to determine the morbidity and mortality pattern of the neonatal admission including the outcome. Materials and Methods: This was a 1-year (March 2015 to February 2016) retrospective study of all the consecutive neonatal admissions in the special care baby unit (SCBU) of Federal Medical Centre Birnin Kudu, Jigawa State, Nigeria. The data obtained were entered into a predesigned pro forma and analyzed appropriately. Results: A total of 205 neonates were admitted to SCBU during the study period with the ratio of the males to females admitted was 2.1:1. The major causes of morbidity were neonatal sepsis (32.2%), birth asphyxia (29.3%), and prematurity (18.5%). In this study, overall mortality rate was 7.16% with birth asphyxia accounting for 13 (40.6%) of the total deaths (χ2 = 1.50, P = 0.68). One hundred and fifty-nine (77%) were discharged, 12 (6%) were discharged against medical advice, while 2 (1%) were referred. Conclusion: Neonatal sepsis, birth asphyxia, and prematurity are the major causes of neonatal morbidity and mortality in this locality.